Pendugaan Umur Simpan Garam Mandi (Bath Salt) Aroma Serreh Menggunakan Metode Accelerated Shelf Life Testing (ASLT) - Putri, Meilinda Cendana; Maflahah, Iffan; Supriyanto, Supriyanto; Asfan, Dian Farida (Rekayasa, 2022)
Salt contains compounds of magnesium chloride, magnesium sulfate, magnesium bromide, and other trace compounds. In general, salt is divided into consumption salt and industrial salt. Bath salt is a salt product that dissolves in water and reduces wrinkles on the hands. The constituent components of bath salts are Epsom salt, sodium bicarbonate, SLES, cornstarch, olive oil, citronella oil, and alcohol, the packaging used is glass packaging. Shelf life is done by accelerating the degradation reaction using high temperature storage and simulating the data obtained. The purpose of this study was to determine the quality characteristics of bath salts before and after storage and to determine the shelf life of bath salts with the aroma of lemongrass. This research was conducted at the Quality Analysis Lab of the Agricultural Industrial Technology Study Program, Faculty of Agriculture, Trunojoyo University, Madura from September to October 2021. Shelf life was estimated using the Arrhenius method. Based on research at a temperature of 28, the shelf life of bath salts is 180.86 or 6 months 1 day, while at a temperature of 35 is 85.85 or 2 months 26 days. It is proven by the value of the shelf life which is getting shorter with the higher the storage temperature. An increase in temperature causes a greater rate of reaction